Correlations between jump measures and competitive performance remain stable over time in top-level sprinters - Loturco, I.; Fernandes, V.; Boullosa, D. A.; Siqueira, F.; Nakaya, K.; Carraco, D.; Reis, V. P.; Pereira, L. A.; McGuigan, M. R. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: We examined the relationships between jump performance measures, sprint tests, and 100-m competition times in 11 top-level sprinters during two successive competitive 4-week mesocycles. METHODS: Physical tests were performed 7-12 days before 3 sequential competitions. Sprinters completed standing long jump, squat and countermovement jumps, and 60-m sprint tests on each occasion. A repeated measures analysis of variance was used to compare the physical assessments and actual competition results among the three moments. A Pearson product-moment correlation coefficient was used to analyze the relationships between the multiple variables over the consecutive mesocycles. Significance level was set at P<0.05. RESULTS: No significant differences were observed among the periods for any jump or sprint performance measure (ES ranging from 0.02 to 0.33; P>0.05). Very large to nearly perfect correlations were observed for all sprint and jump variables and 100-m dash times in the three moments analyzed (P<0.05). CONCLUSIONS: Our data indicate that simple jump measures can be prospectively used to monitor sprint performance. Notably, the standing long jump test was the most consistently related to 100-m time. This simple strategy may help track and field coaches to better adjust the competitive approach of their sprinters, thus optimizing their peak performance.